Balancing entrepreneurial values with social impact - Raikundalia, Sheena (Technical Centre for Agricultural and Rural Cooperation, 2016)
Social entrepreneurs in Africa have developed innovative ICT-enabled models for agriculture with the aim of combining profit with inclusive rural development. Their main challenges are scaling-up and earning an income while serving the poorest rural communities.